PENGGUNAAN SUKU KATA DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN PADA PESERTA DIDIK SDN PANDEGLANG 7 - Yasyifa Azhar Syauqiyyah; Encep Andriana; Siti Rokmanah (STKIP Subang, 2023)
This study aims to describe the use of syllables in improving students’ reading skills in class II SDN Pandeglang 7. This research was also made to determine the use of syllables in improving students’ reading skills in class II. In this study uses a qualitative type of case study which is a study where the researcher digs a certain phenomenon (case) in a time and activity (program, evening, process, institution or social group) and collects information in depth and uses various data collection procedures during a certain period. The results of this study are the use of syllables’ methods and also effective learning media in improving the beginning of students, this is evident from the reading process of reading students who have increased. The teacher also has a program for students who have not been fluent reading, namely KOMBEL, which is carried out after the class hour is over. and schools also have a reading program is GEMARIBU which is able to improve students’ reading skills and build habits to read.